Recent Advances in the Pathobiology of Hodgkin's Lymphoma: Potential Impact on Diagnostic, Predictive, and Therapeutic Strategies - Diponkar Banerjee (Advances in Hematology)
From its first description by Thomas Hodgkin in 1832, Hodgkin's disease, now called Hodgkin's lymphoma, has continued to be a fascinating neoplasm even to this day. In this review, historical aspects, epidemiology, diagnosis, tumor biology, new observations related to host-microenvironment interactions, gene copy number variation, and gene expression profiling in this complex neoplasm are described, with an exploration of chemoresistance mechanisms and potential novel therapies for refractory disease.